Microparticles from apoptotic RAW 264.7 macrophage cells carry tumour necrosis factor‐α functionally active on cardiomyocytes from adult mice. Issue 1 (23rd October 2015) - Milbank, Edward; Soleti, Raffaella; Martinez, Emilie; Lahouel, Badreddine; Hilairet, Grégory; Martinez, M. Carmen; Andriantsitohaina, Ramaroson; Noireaud, Jacques
Abstract : After ischaemic injury and in patients with atherosclerosis, the pool of inflammatory macrophages is enlarged in the heart and in atherosclerotic plaques. Monocyte/macrophage‐derived microparticles (MPs) are part of the pathological process of unstable atherosclerotic plaques. The present study focused on effects of MPs, produced by apoptotic murine RAW 264.7 macrophage cell line, in adult murine cardiomyocytes. Flow cytometry and western blot analysis showed that these MPs contained the soluble form of tumour necrosis factor alpha (TNF‐α). Cardiomyocyte sarcomere shortening amplitudes and kinetics were reduced within 5 min of exposure to these MPs. Conversely, Ca 2+ transient amplitude and kinetics were not modified. The contractile effects of MPs were completely prevented after pretreatment with nitric oxide synthase, guanylate cyclase or TNF‐α inhibitors as well as blocking TNF‐α receptor 1 with neutralizing antibody. Microscopy showed that, after 1 h, MPs were clearly surrounding rod‐shaped cardiomyocytes, and after 2 h they were internalized into cardiomyocytes undergoing apoptosis. After 4 h of treatment with MPs, cardiomyocytes expressed increased caspase‐3, caspase‐8, Bax and cytochrome C. Thus, MPs from apoptotic macrophages induced a negative inotropic effect and slowing of both contraction and relaxation, similar to that observed in the presence of TNF‐α. The use of specific inhibitors strongly suggests that TNF‐α receptors and the guanylate cyclase/cGMP/PKG pathway were involved in the functional responses to these MPs and that the mitochondrial intrinsic pathway was implicated in their proapoptotic effects. These data suggest that MPs issued from activated macrophages carrying TNF‐α could contribute to propagation of inflammatory signals leading to myocardial infarction.